Oratorical Principles of Educating Youth Audiences in the Turkic Worldview - Malikova, A.M.; Makulbekov, A.T.; Abdalieva, G.K. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
This article will make a pioneering attempt to perform a scientific analysis of the Turkic worldview in the context of oratory principles of educating youth audiences. We will analyze cultural upbringing attitudes and principles through the prism of the historical aspect. We consider it necessary to make a brief overview of the historical and logical background of the Eastern Muslim culture. History testifies that social, economic, political, and cultural life of Turkic peoples has been closely intertwined since ancient times. It goes without saying that the Eastern Muslim culture was nourished by the roots of the spiritual and cultural heritage of the ancient Turkic peoples. Every year more and more researchers are attracted to historical, social and political, philosophical, cultural and moral, literary and poetic, didactic, linguistic, pedagogical, and psychological aspects of the cultural heritage. It is the first time when the essence of the phenomenon of the Turkic-speaking cultural heritage expressed in the oratorical word as well as its cultural principles and attitudes become the object of cultural analysis. When analyzing the eastern peoples’ standard of speech, literature, social life, architecture, and cultural aspects, we discover their similarities. If we look at the common ground of the Turkic society, i.e. the ancient Turkic culture and the art of speech in the context of Eastern culture, we easily reveal their shared historical roots. As evidence, archeological studies at hundreds of sites and settlements within the territory of modern Kazakhstan show cultural similarities with the eastern countries.
Жастар аудиториясын шешендік өнер контексінде түркі дүниетанымында тәрбиелеудің ықпалы
Влияние ораторского искусства в контексте воспитания молодёжной аудитории в тюркском мировоззрении
Keywords: Turkic worldview; oratory; audience; education; cultural phenomenon; overview; existence; value